Gel de própolis mucoadesivo versus solução de cloridrato de benzidamina na prevenção da mucosite oral em pacientes irradiados em região de cabeça e pescoço.: ensaio clinico, cego, randomizado - fase II. - Vladimir Reimar Augusto de Souza Noronha (2015)
The best known side effects in the oral cavity during radiotherapy for the treatment of cancer in the head and neck, are mucositis and candidiasis. These changes are enhanced by hyposalivation due to changes in the salivary glands. There are many protocols for the control of mucositis, hyposalivation, and oral candidiasis in these patients however, none iscompletely effective. Propolis has analgesic, anti-inflammatory, antifungal and healing activity. These pharmacological characteristics give propolis great potential to prevent changes in the oral cavity of patients undergoing radiotherapy. The aim of this study was to evaluate the effectiveness of the gel containing propolis in preventing mucositis and candidiasis compared with benzydamine hydrochloride. Twenty-six patients were included in this study. Patients were divided into two groups with group 1 used the benzydamine hydrochloride and group 2 gel propolis. Both group used the products three times a day during the whole period of radiotherapy and two weeks after the end of treatment and all patients were evaluated weekly. The results showed that 84.6% of patients were male and 19.2% of patients maintained the habit of smoking and drinking alcohol. The mean dose of radiation was 6466.1 Gys. After the final analysis it was observed that the gel propolis showed a better efficacy in the prevention of mucositis from 17th session of radiotherapy compared to benzydamine hydrochloride group. Seventy-eight percent (78.6%) patients rated the product as well as to indicate 85.7% for patients with the same condition. The study showed that control of inflammation in the oral mucosa by gel containing propolis was better.